Viaje a un Oriente europeo : patrimonio y turismo en Andalucía (1800-1929) / Luis Méndez Rodríguez, Rocío Plaza Orellana, Antonio Zoido Naranjo - Plaza Orellana, RocíoZoido, Antonio (Zoido Naranjo); Méndez Rodríguez, Luis
Bibliografía: p. 265-270